Relationship between cardiovascular endurance and mental toughness among Academy Mokhtar Dahari (AMD) football players / Rozita Abdul Latif ... [et al.] - Abdul Latif, Rozita; Ghazali, Muhammad Syakir; Ab Rahman, Zarizi; Mohamed, Ani Mazlina Dewi; Omar Fauzee, Mohd Sofian (Universiti Teknologi MARA, 2022)
The main purpose of this study was to examine the relationship between cardiovascular endurance and mental toughness among football players of Academy Mokhtar Dahari (AMD). Twenty players were selected as respondents. Data were collected using Yo-Yo test level 1 and Mental Emotional Bodily Toughness (MeBTough) Questionnaires (Mark, 2008). This study showed that cardiovascular endurance parameters were good (M=2064.00, SD=251.45), while mental toughness measures appeared moderate (M=126.55, SD=15.10). Moreover, this study has indicated no significant relationship between cardiovascular endurance and mental toughness (r=0.38, p>0.05). Analyze showed that a 10-week athlete’s training does not significantly influence the relationship between cardiovascular endurance and mental toughness even if the athletes have attained high cardiovascular endurance. The result showed that the duration of the training, experience, and effort to enhance both physiological and psychological skills needed to improve mental toughness among sports players.